2017
DOI: 10.1177/2474126417724655
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Elevated Intraocular Pressure on First Day Postoperative Review Following Pars Plana Vitrectomy

Abstract: To assess the relationship between day one post-operative intra-ocular pressure and patient demographic information, lens status, tamponade medium (air, perfluoroethane, sulfur hexafluoride) and laser treatment. Methods: A prospective observational study of all patients undergoing pars plana vitrectomy by a single surgeon within one case study. All patients had intraocular pressure recorded one-day after surgery. None of the patients had postoperative antiglaucoma medications. All patients undergoing pars plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Increased IOP is a common complication of vitrectomy during the early postoperative stage [1][2][3][4][5][6]. The risk factors for IOP include postoperative inflammation, the use of gaseous methods of endotamponade, excessive or poorly directed laser photocoagulation, and transient choroidal edema [1,[3][4][5][6][7][8]. Previous clinical studies have shown that up to half of the patients developed IOP within two weeks following vitrectomy for macular hole [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Increased IOP is a common complication of vitrectomy during the early postoperative stage [1][2][3][4][5][6]. The risk factors for IOP include postoperative inflammation, the use of gaseous methods of endotamponade, excessive or poorly directed laser photocoagulation, and transient choroidal edema [1,[3][4][5][6][7][8]. Previous clinical studies have shown that up to half of the patients developed IOP within two weeks following vitrectomy for macular hole [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…A significant, common complication of PPV is a repeated rise in IOP above the normal limit, i.e., 21 mmHg. The risk factors include, among others, postoperative infection, use of gas as endotamponade, excessive or incorrectly directed laser coagulation and transient cystoid macular edema [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pars plana vitrectomy (PPV) is a surgical procedure that can be used to treat retinal and vitreous body diseases, such as retinal detachment, epiretinal membranes, macular holes, vitreoretinal traction, or hemorrhage into the vitreous chamber [15,16]. Common complications following PPV include an increase in IOP, which is predisposed by postoperative inflammation, the type of endotamponade used, and excessive or incorrectly directed laser coagulation [17][18][19][20]. Two types of transscleral cyclophotocoagulation (TSCPC), which are used to lower IOP after PPV, can be differentiated, namely traditional continuous-wave (CW-TSCPC) and, more recently, MicroPulse TSCPC (lP-TSCPC) (Iridex, Mountain View, CA, USA).…”
Section: Introductionmentioning
confidence: 99%